A method for preparing battery-grade anhydrous lithium acetate by using crude lithium sulfate crystals

CN122977951APending Publication Date: 2026-10-27BAIJIERUI (JING MEN) ADVANCED MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611050554.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有技术中制备电池级无水醋酸锂的方法主要存在两类缺陷:一类是以工业级氢氧化锂为锂源,与冰醋酸进行中和反应,经过滤除杂、浓缩烘干制得产品,该方法虽能保证产品纯度,但氢氧化锂原料成本高昂,导致产品生产的经济效益低下,如专利申请CN103739475A;另一类是利用磷酸铁锂废料直接经醋酸酸浸提锂,再分步除杂、浓缩烘干制得无水醋酸锂,该方法虽降低了原料成本,但醋酸为弱酸,对锂的浸取效果差,锂收率低,且酸浸过程需添加双氧水作为氧化剂,工艺步骤繁琐,后续除杂难度大,经济性和工业化可行性差,如专利申请CN118420457A

Benefits of technology

[0015]本发明以报废锂电池回收的粗品硫酸锂晶体为锂源,开发出一套原料成本低、除杂工艺简洁、锂收率高、产品纯度达标的电池级无水醋酸锂制备方法,通过分步化学沉淀脱除硫酸根、草酸络合深度除杂,结合精准的浓缩结晶工艺,实现了粗品硫酸锂的高值化利用,解决了现有技术的痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to lithium battery recycling and fine chemical preparation technical field, disclose a kind of method for preparing battery grade anhydrous lithium acetate using crude lithium sulfate crystal, comprising: (1) crude lithium sulfate is mixed with water, to obtain lithium-containing material, to obtain first filtrate by filtration;(2) first filtrate is mixed with calcium acetate first heat preservation reaction, to obtain second filtrate by filtration;(3) second filtrate is mixed with barium acetate and carries out second heat preservation reaction, to obtain third filtrate by filtration;(4) third filtrate is mixed with oxalic acid, control system pH value is greater than or equal to 7, to carry out complexation reaction, after finishing, to obtain lithium acetate pure liquid by filtration;(5) lithium acetate pure liquid is concentrated to obtain concentrate, the concentrate is crystallized, solid-liquid separation is carried out, to obtain lithium acetate wet material, lithium acetate wet material is dried to obtain battery grade anhydrous lithium acetate.The method process step is simple and easy to operate, impurity removal effect is good, the product prepared meets battery grade standard, lithium yield is high, suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery recycling technology, specifically to a method for preparing battery-grade anhydrous lithium acetate using crude lithium sulfate crystals. Background Technology

[0002] Lithium acetate is an important colorless crystalline inorganic salt. In the lithium battery industry, it is used as a core electrolyte additive to effectively improve the ionic conductivity of lithium battery electrolytes and enhance the charge-discharge performance and cycle life of batteries. At the same time, it is widely used in organic synthesis as a high-efficiency catalyst and in the pharmaceutical industry as a diuretic. All of these applications place extremely high battery-grade purity requirements on lithium acetate.

[0003] Existing methods for preparing battery-grade anhydrous lithium acetate mainly suffer from two types of defects: one type uses industrial-grade lithium hydroxide as the lithium source, which is neutralized with glacial acetic acid, and then filtered, concentrated, and dried to obtain the product. Although this method can ensure product purity, the cost of lithium hydroxide raw materials is high, resulting in low economic efficiency in product production, as shown in patent application CN103739475A. The other type uses lithium iron phosphate waste to directly extract lithium through acetic acid leaching, followed by stepwise impurity removal, concentration, and drying to obtain anhydrous lithium acetate. Although this method reduces raw material costs, acetic acid is a weak acid, which has a poor leaching effect on lithium, resulting in low lithium yield. Furthermore, the acid leaching process requires the addition of hydrogen peroxide as an oxidant, making the process steps cumbersome and subsequent impurity removal difficult, resulting in poor economic efficiency and industrial feasibility, as shown in patent application CN118420457A. Summary of the Invention

[0004] The purpose of this invention is to overcome the above-mentioned problems in the prior art and provide a method for preparing battery-grade anhydrous lithium acetate using crude lithium sulfate crystals. This method uses readily available and low-cost raw materials, has simple and easy-to-operate process steps, good impurity removal effect, and the purity of the obtained product meets battery-grade standards. It also has a high lithium yield and is suitable for large-scale industrial production.

[0005] To achieve the above objectives, the present invention provides a method for preparing battery-grade anhydrous lithium acetate using crude lithium sulfate crystals, comprising: (1) Crude lithium sulfate is mixed with water to obtain a lithium-containing material with a Li element concentration of 12-40 g / L. The lithium-containing material is filtered to obtain the first filtrate. (2) Mix the first filtrate with calcium acetate, then carry out the first heat preservation reaction, and then filter to obtain the second filtrate; the conditions for the first heat preservation reaction include: temperature of 50-80℃ and time of 0.2-0.8h; (3) Mix the second filtrate with barium acetate, then carry out the second heat preservation reaction, and then filter to obtain the third filtrate; (4) Mix the third filtrate with oxalic acid, then control the pH of the system to ≥7, and then carry out a complexation reaction. After the complexation reaction is completed, filter to obtain lithium acetate solution. (5) Concentrate the lithium acetate solution to obtain a concentrate, crystallize the concentrate, and then separate the solid and liquid to obtain a wet lithium acetate material. Dry the wet lithium acetate material to obtain battery-grade anhydrous lithium acetate.

[0006] Preferably, in step (1), the crude lithium sulfate comprises lithium sulfate and unavoidable impurities. The crude lithium sulfate contains 9.8-11.2 wt% lithium sulfate (calculated as Li), 100-1000 ppm Na, 100-1000 ppm K, 10-1000 ppm Ca, 2-100 ppm Fe, 20-200 ppm Mg, and Cl. - The content is 50-1000ppm.

[0007] Preferably, in step (1), the concentration of Li element in the lithium-containing material is 15-35 g / L.

[0008] Preferably, in step (2), the amount of calcium acetate used is 1-1.5 times the molar equivalent of sulfate in the first filtrate.

[0009] Preferably, the conditions for the first heat preservation reaction in step (2) include: a temperature of 50-60℃ and a time of 0.5-0.8h.

[0010] Preferably, in step (3), the amount of barium acetate used is 1-1.5 times the molar equivalent of sulfate in the second filtrate.

[0011] Preferably, in step (3), the conditions for the second heat preservation reaction include: a temperature of 50-60℃ and a time of 0.5-1h.

[0012] Preferably, in step (4), the pH value of the control system is 7-7.5.

[0013] Preferably, in step (4), the conditions for the complexation reaction include: a temperature of 80-90℃ and a time of 0.5-1h.

[0014] Preferably, in step (5), the concentration is a temperature-increasing concentration.

[0015] This invention uses crude lithium sulfate crystals recycled from waste lithium batteries as the lithium source and develops a method for preparing battery-grade anhydrous lithium acetate that features low raw material costs, simple impurity removal process, high lithium yield, and product purity. By removing sulfate through stepwise chemical precipitation and deeply removing impurities through oxalic acid complexation, combined with a precise concentration and crystallization process, the high-value utilization of crude lithium sulfate is achieved, solving the pain points of existing technologies. Detailed Implementation

[0016] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0017] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0018] This invention provides a method for preparing battery-grade anhydrous lithium acetate using crude lithium sulfate crystals, comprising: (1) Crude lithium sulfate is mixed with water to obtain a lithium-containing material with a Li element concentration of 12-40 g / L. The lithium-containing material is filtered to obtain the first filtrate. (2) Mix the first filtrate with calcium acetate, then carry out the first heat preservation reaction, and then filter to obtain the second filtrate; the conditions for the first heat preservation reaction include: temperature of 50-80℃ and time of 0.2-0.8h; (3) Mix the second filtrate with barium acetate, then carry out the second heat preservation reaction, and then filter to obtain the third filtrate; (4) Mix the third filtrate with oxalic acid, then control the pH of the system to ≥7, and then carry out a complexation reaction. After the complexation reaction is completed, filter to obtain lithium acetate solution. (5) Concentrate the lithium acetate solution to obtain a concentrate, crystallize the concentrate, and then separate the solid and liquid to obtain a wet lithium acetate material. Dry the wet lithium acetate material to obtain battery-grade anhydrous lithium acetate.

[0019] In step (1) of this invention, crude lithium sulfate is obtained by recycling discarded lithium batteries. The crude lithium sulfate includes lithium sulfate and unavoidable impurities. The content of lithium sulfate in the crude lithium sulfate, calculated as Li, is 9.8-11.2 wt%, Na is 100-1000 ppm, K is 100-1000 ppm, Ca is 10-1000 ppm, Fe is 2-100 ppm, Mg is 20-200 ppm, and Cl... - The content is 50-1000 ppm; including Na, K, Ca, Fe, Mg and Cl elements. - All of them are impurities.

[0020] In the preferred embodiment, in step (1), the Li element concentration in the lithium-containing material is 15-35 g / L; within this range, the impurity removal effect, lithium loss minimization, and energy consumption reduction during subsequent evaporation and concentration can be balanced. If the lithium concentration is too high, the more lithium entrained in the calcium slag and barium slag after chemical impurity removal, the greater the lithium loss; if the lithium concentration is too low, the energy consumption for subsequent evaporation and concentration will be higher.

[0021] In a specific implementation, in step (1), a 5-10 μm filter membrane is used to filter the lithium-containing material to remove mechanical impurities and insoluble substances from the lithium-containing material, and a clear first filtrate is obtained.

[0022] Preferably, in step (2) of the present invention, the amount of calcium acetate used is 1-1.5 times the molar equivalent of sulfate in the first filtrate.

[0023] In a preferred embodiment, the conditions for the first heat preservation reaction in step (2) include: a temperature of 50-60°C and a time of 0.5-0.8h. Under these conditions, calcium acetate and sulfate can react fully to generate calcium sulfate precipitate. After the first heat preservation reaction is completed, the mixture is filtered to obtain a second filtrate and calcium sulfate residue. The calcium sulfate residue can be collected and reused as an industrial raw material.

[0024] In step (3), some sulfate ions will remain in the second filtrate. To remove them completely, the amount of barium acetate used is 1-1.5 times the molar equivalent of sulfate ions in the second filtrate.

[0025] In this invention, the combination of calcium acetate used in step (2) and barium acetate used in step (3) can deeply remove sulfate ions, and the small amount of residual calcium and barium can be easily removed with oxalic acid.

[0026] Further, in step (3), the conditions for the second heat preservation reaction include: a temperature of 50-60℃ and a time of 0.5-1h; under these conditions, the residual sulfate ions react fully with barium acetate to generate barium sulfate precipitate. After the second heat preservation reaction is completed, the mixture is filtered to obtain the third filtrate with deep removal of sulfate ions and a small amount of barium sulfate residue. The barium sulfate residue can be recycled after harmless treatment.

[0027] Since calcium sulfate has a certain solubility, if the sulfate ions are to be removed to the maximum extent during the initial impurity removal, calcium acetate and barium acetate are often used in excess in steps (2) and (3). Therefore, the obtained third filtrate will still contain some impurities such as calcium acetate and barium acetate. In order to remove the residual calcium acetate and barium acetate, oxalic acid is added in step (4) to remove the residual calcium and barium (even if lithium oxalate is generated, it will not cause lithium loss because lithium oxalate has high solubility). The amount of oxalic acid added is adjusted according to the content of metal impurities in the third filtrate. In the preferred case, the amount of oxalic acid is 1-1.5 times the total molar equivalent of calcium acetate and barium acetate in the third filtrate.

[0028] In a further preferred embodiment of the present invention, in step (4), the pH value of the system is controlled to be 7-7.5.

[0029] In a specific implementation, in step (4), one or more of lithium hydroxide, ammonia and lithium carbonate can be used to adjust the pH of the system to 7-7.5.

[0030] In a preferred embodiment, the conditions for the complexation reaction in step (4) of the present invention include: a temperature of 80-90°C and a time of 0.5-1h. Under these conditions, oxalic acid reacts with metal impurities such as Ca, Mg, and Fe in the third filtrate to form an insoluble oxalate precipitate. After the complexation reaction is completed, the solution is filtered to remove all precipitated impurities and obtain a high-purity lithium acetate solution.

[0031] In step (5) of this invention, the concentration is a heating concentration, which is usually carried out by heating under normal pressure. Specifically, the lithium acetate solution is heated and will be continuously concentrated during the heating process. After the temperature reaches 110-120℃, the concentration ends and the heating is stopped to obtain the concentrate. The concentrate is then cooled to crystallize. During the crystallization process, stirring is maintained throughout and the stirring rate is controlled at 50-80 r / min to ensure uniform crystal growth. After the temperature drops to 30-35℃, the crystallization is completed. Then, the mixture is centrifuged at 3000-4000 r / min for 10-15 min to obtain wet lithium acetate. Then, it is dried at 120-130℃ for 4 h to obtain battery-grade anhydrous lithium acetate.

[0032] In this invention, crude lithium sulfate crystals are recycled products from waste lithium batteries, which significantly reduces the cost of lithium sources compared to lithium hydroxide. A stepwise addition of calcium acetate and barium acetate is used to remove sulfate ions, resulting in more thorough removal compared to a single precipitant, with milder reaction conditions and shorter reaction time. The oxalic acid impurity removal process precisely controls pH and temperature, achieving deep complexation removal of metallic impurities without introducing new harmful impurities. Precise temperature control during the concentration and crystallization process ensures uniform growth of lithium acetate crystals and avoids impurity encapsulation. Subsequent drying process parameters are matched to ensure the product is anhydrous and retains its purity.

[0033] The battery-grade anhydrous lithium acetate product obtained by this invention has a CH3COOLi content ≥ 99.9 wt%, and the contents of each impurity (ppm) are controlled within the following limits: Na ≤ 50 ppm, K ≤ 50 ppm, Ca ≤ 100 ppm, Mg ≤ 10 ppm, Fe ≤ 10 ppm, and SO4 ≤ 10 ppm. 2- ≤100ppm, Cl - With ≤100ppm and water-insoluble matter ≤100ppm, the lithium yield can reach 94.5%-96.1%, fully meeting the battery-grade standard requirements of the lithium battery industry for lithium acetate.

[0034] The present invention will be described in detail below through embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following embodiments are commercially available.

[0035] The crude lithium sulfate used in the following examples is a recycled product from waste lithium batteries. The lithium sulfate content (calculated as Li) is 10.2 wt%, and the impurity content (ppm) is as follows: Na 125.6 ppm, K 133.9 ppm, Ca 12.6 ppm, Fe 2.5 ppm, Mg 105.3 ppm, Cl... - The content was 52 ppm.

[0036] Example 1 (1) 200g of crude lithium sulfate was mixed and stirred with 680mL of pure water to obtain a lithium-containing material with a Li element concentration of 30g / L. The lithium-containing material was filtered through an 8μm filter membrane to remove mechanical impurities and insoluble matter, and 650mL of clear first filtrate was obtained. (2) Add 249.1g of industrial grade calcium acetate (purity 99%) to the first filtrate and mix (the amount of calcium acetate is 1.05 times the molar equivalent of sulfate in the first filtrate), then heat to 60℃ and carry out the first heat preservation reaction under stirring. The first heat preservation reaction time is 0.5h. Then filter precisely to obtain 620mL of the second filtrate. (3) Add 2.7g of industrial-grade barium acetate (purity 99%) to the second filtrate and mix (the amount of barium acetate is 1 times the molar equivalent of sulfate in the second filtrate). Then carry out the second heat preservation reaction at 60℃ under stirring for 0.5h. Then filter precisely to obtain 610mL of the third filtrate. (4) Add 1g of industrial grade oxalic acid (99% purity) to the third filtrate and mix (the amount of oxalic acid is 1 times the total molar equivalent of calcium acetate and barium acetate in the third filtrate). Then add ammonia water to control the pH of the system to 7. Then heat to 80℃ to carry out the complexation reaction. The complexation reaction time is 0.5h. After the complexation reaction is completed, filter precisely to obtain lithium acetate solution. (5) Transfer the lithium acetate solution to a concentration kettle and heat it to concentrate (heat the lithium acetate solution. During the heating process, the lithium acetate solution will continue to concentrate. After the temperature reaches 120°C, the concentration will end and the heating will stop). Obtain the concentrate. Then, introduce tap water into the jacket of the concentration kettle to cool the concentrate for crystallization. During the crystallization process, keep stirring throughout and control the stirring rate at 60 r / min to ensure uniform crystal growth. After cooling to 30°C, the crystallization is completed. Then, centrifuge at 3500 r / min for 12 min to obtain wet lithium acetate. Then, dry it at 125°C for 4 h to obtain 181.7 g of battery-grade anhydrous lithium acetate.

[0037] Example 2 (1) Mix 200g of crude lithium sulfate with 1020mL of pure water and stir to dissolve, and obtain a lithium-containing material with a Li element concentration of 20g / L. Filter the lithium-containing material through an 8μm filter membrane to remove mechanical impurities and insoluble matter, and obtain 1000mL of clear first filtrate. (2) Add 261g of industrial grade calcium acetate (purity 99%) to the first filtrate and mix (the amount of calcium acetate is 1.1 times the molar equivalent of sulfate in the first filtrate). Then heat to 60℃ and carry out the first heat preservation reaction under stirring. The first heat preservation reaction time is 0.5h. Then filter precisely to obtain 960mL of the second filtrate. (3) Add 2.9g of industrial grade barium acetate (purity 99%) to the second filtrate and mix (the amount of barium acetate is 1.1 times the molar equivalent of sulfate in the second filtrate). Then carry out the second heat preservation reaction at 60℃ under stirring for 0.5h. Then filter precisely to obtain 950mL of the third filtrate. (4) Add 2.1g of industrial grade oxalic acid (99% purity) to the third filtrate and mix (the amount of oxalic acid is 1 times the total molar equivalent of calcium acetate and barium acetate in the third filtrate). Then add ammonia water to control the pH of the system to 7. Then heat to 80℃ to carry out the complexation reaction. The complexation reaction time is 0.5h. After the complexation reaction is completed, filter precisely to obtain lithium acetate solution. (5) Transfer the lithium acetate solution to a concentration kettle and heat it to concentrate (heat the lithium acetate solution. During the heating process, the lithium acetate solution will continue to concentrate. After the temperature reaches 115°C, the concentration will end and the heating will stop). Obtain the concentrate. Then, introduce tap water into the jacket of the concentration kettle to cool the concentrate for crystallization. During the crystallization process, keep stirring throughout and control the stirring rate at 80 r / min to ensure uniform crystal growth. After cooling to 35°C, the crystallization is completed. Then, centrifuge at 3500 r / min for 12 min to obtain wet lithium acetate. Then, dry it at 125°C for 4 h to obtain 184.6 g of battery-grade anhydrous lithium acetate.

[0038] Comparative Example 1 The method was implemented according to Example 1, except that in step (2), calcium acetate was replaced with the same amount of industrial-grade calcium chloride (99% purity), and finally 152.3g of anhydrous lithium acetate was obtained.

[0039] Comparative Example 2 The method of Example 1 was implemented, except that in step (2), calcium acetate was replaced with the same amount of industrial-grade calcium carbonate (99% purity), and 165.8g of anhydrous lithium acetate was finally obtained.

[0040] Comparative Example 3 The method was implemented according to Example 1, except that in step (1), 200g of crude lithium sulfate was mixed and stirred with 2040mL of pure water to obtain a lithium-containing material with a Li element concentration of 10g / L; in step (2), the temperature of the first heat preservation reaction was 40℃ and the time was 1h; and finally, 170.2g of anhydrous lithium acetate was obtained.

[0041] Test Example 1 The anhydrous lithium acetate products of Examples 1-2 and Comparative Examples 1-3 were tested, and the test results and corresponding test methods are shown in Table 1 and Table 2, respectively.

[0042] Table 1 Table 2 Note: Lithium yield = (mass of lithium in anhydrous lithium acetate / mass of lithium in raw lithium sulfate) 100% As can be seen from Tables 1 and 2, compared with Example 1, the product in Comparative Example 1 has more impurities and a lower lithium yield. This is because calcium chloride easily introduces a large amount of Cl. - Impurities are present, and the calcium sulfate precipitate generated in the reaction easily forms a co-precipitate colloid with calcium chloride, making filtration difficult. Sulfate ions are not completely removed, and the encapsulation of lithium ions causes a serious loss in lithium yield. Furthermore, the purity of the product cannot meet battery-grade standards.

[0043] Compared with Example 1, the product in Comparative Example 2 had more impurities and a lower lithium yield. This is because calcium carbonate has poor water solubility, a slow dissociation rate in the system, and insufficient reaction with sulfate, resulting in a low sulfate removal rate. Furthermore, unreacted calcium carbonate introduces CO3. 2- Impurities are present, and calcium carbonate particles easily adsorb lithium ions, resulting in a loss of lithium yield. The purity and yield of the product do not meet the level of this invention.

[0044] Compared with Example 1, the product in Comparative Example 3 also had more impurities, and the lithium yield was lower than that in Example 1. This is because the reaction rate of calcium acetate was significantly reduced after deviating from the lithium concentration, temperature, and reaction time parameters of the present invention, the sulfate removal effect was reduced, and the low concentration system would increase the energy consumption of subsequent concentration. Long stirring time would easily cause secondary dissolution of crystal precipitate, resulting in a decrease in both lithium yield and impurity removal effect. This confirms the uniqueness and optimality of the parameter combination of the present invention.

[0045] The above results show that the method of the present invention has the following beneficial effects: 1) This invention uses crude lithium sulfate recovered from waste lithium batteries as the lithium source, and the raw material cost is much lower than that of lithium hydroxide. At the same time, it realizes the high-value recycling and utilization of waste lithium batteries, which is in line with the green and environmentally friendly industrial development concept. 2) The process steps are simple. The impurity removal process adopts the method of "calcium acetate + barium acetate stepwise desulfate + oxalic acid complexation to remove metal impurities". The reaction conditions are mild and the reaction time is short. No complicated equipment is required, and it is easy to realize continuous industrial production. 3) Thorough impurity removal effect: Stepwise precipitation to remove sulfate ions avoids the problem of incomplete removal by a single precipitant. Oxalic acid complexation to remove impurities is carried out under near-neutral conditions, accurately removing metal impurities without introducing new impurities. The product purity is 99.9%, meeting battery-grade standards. 4) High lithium yield: This invention has no additional lithium loss throughout the process, and the lithium yield can reach 94.5%-96.1%, which is far higher than the existing technology of lithium extraction by acetic acid leaching, thus improving the economic benefits of production. 5) The calcium sulfate slag and barium sulfate slag generated during the production process are both easily separable solid waste residues with no harmful waste liquid discharge. The waste residues can be recycled and reused after simple treatment, which is environmentally friendly and reduces the cost of treating waste.

[0046] It should be understood that any parts not described in detail in this specification belong to the prior art.

[0047] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing battery-grade anhydrous lithium acetate using crude lithium sulfate crystals, characterized in that, include: (1) Crude lithium sulfate is mixed with water to obtain a lithium-containing material with a Li element concentration of 12-40 g / L. The lithium-containing material is filtered to obtain the first filtrate. (2) Mix the first filtrate with calcium acetate, then carry out the first heat preservation reaction, and then filter to obtain the second filtrate; The conditions for the first heat preservation reaction include: a temperature of 50-80℃ and a time of 0.2-0.8h; (3) Mix the second filtrate with barium acetate, then carry out the second heat preservation reaction, and then filter to obtain the third filtrate; (4) Mix the third filtrate with oxalic acid, then control the pH of the system to ≥7, and then carry out a complexation reaction. After the complexation reaction is completed, filter to obtain lithium acetate solution. (5) Concentrate the lithium acetate solution to obtain a concentrate, crystallize the concentrate, and then separate the solid and liquid to obtain a wet lithium acetate material. Dry the wet lithium acetate material to obtain battery-grade anhydrous lithium acetate.

2. The method according to claim 1, characterized in that, In step (1), the crude lithium sulfate includes lithium sulfate and unavoidable impurities. The crude lithium sulfate contains 9.8-11.2 wt% lithium sulfate (calculated as Li), 100-1000 ppm Na, 100-1000 ppm K, 10-1000 ppm Ca, 2-100 ppm Fe, 20-200 ppm Mg, and Cl. - The content is 50-1000ppm.

3. The method according to claim 1 or 2, characterized in that, In step (1), the concentration of Li element in the lithium-containing material is 15-35 g / L.

4. The method according to claim 1, characterized in that, In step (2), the amount of calcium acetate used is 1-1.5 times the molar equivalent of sulfate in the first filtrate.

5. The method according to claim 1, characterized in that, The conditions for the first heat preservation reaction in step (2) include: temperature of 50-60℃ and time of 0.5-0.8h.

6. The method according to claim 1, characterized in that, In step (3), the amount of barium acetate used is 1-1.5 times the molar equivalent of sulfate in the second filtrate.

7. The method according to claim 1, characterized in that, In step (3), the conditions for the second heat preservation reaction include: a temperature of 50-60℃ and a time of 0.5-1h.

8. The method according to claim 1, characterized in that, In step (4), the pH value of the control system is controlled to be 7-7.

5.

9. The method according to claim 1 or 8, characterized in that, In step (4), the conditions for the complexation reaction include: a temperature of 80-90℃ and a time of 0.5-1h.

10. The method according to claim 1, characterized in that, In step (5), the concentration is a temperature-increasing concentration.

Citation Information

Patent Citations

  • Method for preparing battery grade anhydrous lithium acetate

    CN103739475A